PSYCHOLOGICAL NATURE OF SATURITY BY THE CONDITIONS OF RESIDENCE IN THE MEGAPOLIS: RESULTS OF AN EMPIRICAL STUDY - Larionov, I. V.; Drobysheva , T. V. (Modern Psychology, 2019)
The article is devoted to the development of a new phenomenon in the field of social psychology of the city - satiety with living conditions in a metropolis. Study involved 87 people aged 18-30. The aim of the study was to identify and analyze the expression of the satiety of young Moscovites by living conditions in the metropolis and its dependence on the sources of experience of this state. It was shown that satiety as a state of the human psyche performs the function of a protective mechanism from an overabundance of a flow of various stimuli from the surrounding world. The satiety with living conditions in the metropolis is a complex state that is caused by variety of phenomena of social life in the urban environment: excessive communication, an abundance of information, overpopulation, forced informatization of the urban environment, high rate of life, etc. It was found that satiety with living conditions in a metropolis has different forms of expression: such as emotional experiences and behavioral reactions. The article outlines perspectives for further research of phenomenon of satiety in living conditions in a megacity in the direction of types, as well as factors and mechanisms of satiety.
Keywords: social psychology of the city, satiety, living conditions in the metropolis, hedonistic, communicative, informational forms of satiety, youth.